Unveiling the Role of Oligosaccharyltransferase STT3B in Colorectal Cancer Tissues: Clinical significance and Molecular Mechanisms Driving the Formation of Tertiary Lymphoid Structures - Caixia Zhang; Bin Wang; Xiaofeng Bian; Youcai Zhao; Xiaobing Yang; Wei Zhao (Immunobiology)
The role of tertiary lymphatic structures (TLS) in anti-tumor response has garnered increasing attention; however, the clinical implications and regulatory mechanisms of various TLS subtypes remain poorly understood. This study investigates the function of the oligosaccharyltransferase subunit STT3B in modulating TLS formation and B cell activity within colorectal cancer (CRC) tissues. Spatial morphology analysis was employed to accurately identify the localization of STT3B expression within TLS. By integrating clinical samples with bioinformatics analyses, we examined the expression levels and distribution patterns of STT3B in the CRC microenvironment and assessed its clinical significance. Transcriptome sequencing, combined with in vitro validation, was utilized to evaluate the effects of STT3B knockdown on B cell functionality. The findings indicated that CRC patients with a high density of STT3B expression in the TLS had a better prognosis. Multicolor fluorescence analysis further demonstrated that the density of STT3B+CD19+ B cells correlated with pathological characteristics and lymph node metastasis status in CRC patients, with higher densities predicting longer disease-free survival. Transcriptome sequencing further demonstrated that STT3B knockdown predominantly impacts B cell metabolic functions. In vitro experiments confirmed that the downregulation of STT3B inhibits the metabolism and proliferation of B cells. These findings suggest that STT3B plays a crucial role in enhancing B cell metabolism and facilitating the development of mature TLS, which is associated with improved prognostic outcomes in patients with CRC.